2011
DOI: 10.5251/ajsir.2011.2.3.332.345
|View full text |Cite
|
Sign up to set email alerts
|

Microwave signal attenuation at 7.2GHz in Rain and Harmattan Weather

Abstract: Line-of-sight (LOS) attenuation at 7.2GHz was measured in Lagos (6 o 26N, 3 o 52E) for twelve months (Aug '08-July'09) using one of the Nigerian Telecommunications radio signal. The measurement was carried out with the intent of highlighting microwave signal attenuation in Harmattan and rain weather conditions. The results are presented in terms of mean signal level, received signal level and fog attenuation, rain attenuation, multipath fading, free space loss and link availability. The observed attenuation va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…After collecting the daily information for many times of the day and for winter and summer seasons which included (fair, cloudy, and rainy days) with different variable values, so the data were arranged in tables showing the values for each of mobile signal and 'TV' satellite signal including corresponding values of other variables at the same time of temperature, humidity and UV index, as well as corresponding weather condition, see Table .1 which show the variation of meteorological variables comparing with mobile signal strength in (dp) unit. The result shows that the weather condition has a clear effect on radio wave signal value, and this is clearly shown on Figure 1 where it shows that rainy days are corresponding with the lowest signal range as compared with other cases because of increasing water intensity in the air that effects on wave transport from the tower to the mobile phone, therefore it leads to lower signal values reaching (15 dp).the result also showed that the cloud can affect on mobile phone signal strength because when compare between two days with different conditions "first one spatially clouded and the second one is fully clouded", then it found that the signal strength is affected by fully clouded day more than its effect with spatially clouded day, so can say that the signal strength always effected by cloud and records approximately (30 dp) but it considered acceptable ratio to make good communication, It is worth noting that previous studies have indicated similar results related to rain intensity and its effect on signal strength [3]. On the other side the days with fair weather correlated with the highest signal strength because of the absence of meteorological obstacles that effect wave transfer, see Figure 1.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…After collecting the daily information for many times of the day and for winter and summer seasons which included (fair, cloudy, and rainy days) with different variable values, so the data were arranged in tables showing the values for each of mobile signal and 'TV' satellite signal including corresponding values of other variables at the same time of temperature, humidity and UV index, as well as corresponding weather condition, see Table .1 which show the variation of meteorological variables comparing with mobile signal strength in (dp) unit. The result shows that the weather condition has a clear effect on radio wave signal value, and this is clearly shown on Figure 1 where it shows that rainy days are corresponding with the lowest signal range as compared with other cases because of increasing water intensity in the air that effects on wave transport from the tower to the mobile phone, therefore it leads to lower signal values reaching (15 dp).the result also showed that the cloud can affect on mobile phone signal strength because when compare between two days with different conditions "first one spatially clouded and the second one is fully clouded", then it found that the signal strength is affected by fully clouded day more than its effect with spatially clouded day, so can say that the signal strength always effected by cloud and records approximately (30 dp) but it considered acceptable ratio to make good communication, It is worth noting that previous studies have indicated similar results related to rain intensity and its effect on signal strength [3]. On the other side the days with fair weather correlated with the highest signal strength because of the absence of meteorological obstacles that effect wave transfer, see Figure 1.…”
Section: Resultsmentioning
confidence: 76%
“…The way that control wave transferring from transmitter device to receiver device is considered very important when starting to make a new communication system, therefore it is very useful to take into account the nature of the new place [2]. The electromagnetic wave is involved inside the electromagnetic spectrum which extended from shorter to longer wavelength [3]. Humans were able to exploit all parts of the electromagnetic spectrum at various levels and in many medical, engineering and space communications fields [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tese values indicate that the designed link is highly reliable, ensuring the establishment of a quality service. Te percentage availability and fade margin provide assurance of the link's quality and reliability, guaranteeing interferencefree communication [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…However, rain attenuation and the associated rain fade have continued to pose serious challenges to communication at microwave frequencies. In the design of telecommunication systems, the dynamic characteristics of fading due to atmospheric effects are essential in order to optimize system capacity and meet quality and reliability of signal reception (Shoewu and Edeko 2011).…”
Section: Introductionmentioning
confidence: 99%